How to Learn to Stop Worrying and Love the Job Market. (23rd January 2015) - Jacobson, Sarah
<x xml:space="preserve">Abstract</x> This article conveys information and advice about the job market process for candidates completing their PhDs in economics in the United States. I discuss the mechanics of the job market process in great detail, from the preparatory work before the market starts to the steps after accepting an offer. Throughout, I answer common job market‐related questions and discuss ways to make the process more manageable and less stressful. The focus is on students from non‐top‐tier universities, although the advice applies equally well to students from top schools.